Two-stage surgical management for chronic volar lunate dislocation: a case report - Zhang, Lin; Yu, Yang; Yang, Fuyin; Peng, Jiaze; Li, Jinglin; Huang, Xianpeng; Deng, Xuan; Yang, Xuxu; Yang, Lidan (Frontiers in Surgery, 2026)
BackgroundVolar lunate dislocations typically result from high-energy trauma involving dorsiflexion and ulnar deviation forces, and are frequently accompanied by peri-lunate fractures. Without timely intervention, these injuries often progress to a chronic stage, conventionally defined as presentation beyond 6 weeks. Conventional single-stage surgical approaches often yield suboptimal outcomes for such complex, chronic presentations.Case presentationWe report a 34-year-old male with persistent right wrist pain and restricted mobility for 11 months following a fall. Diagnostic imaging confirmed severe chronic volar lunate dislocation. A two-stage surgical protocol—comprising preoperative progressive wrist distraction followed by open reduction, internal fixation, and ligament reconstruction—successfully restored carpal alignment while preserving a functional range of motion. At one-year follow-up, the patient demonstrated excellent clinical recovery.ConclusionThis case demonstrates that for severe chronic volar lunate dislocations of exceptionally long duration, a two-stage strategy incorporating progressive distraction and subsequent reconstruction is a viable and effective approach. It successfully addressed the challenges of extreme chronicity, achieving anatomical reduction and functional recovery where standard methods might fail.